Foreign body ingestion in an infant: A high index of suspicion is required - Luqman Afiq Mohamad Ishak; Kee Guan Khor; Shi Nee Tan (Wiley, 2019)
Abstract Introduction The incidence of foreign body ingestion in the upper gastrointestinal tract accounts for 75%-85% of foreign body ingestions in pediatric patients. Case presentation An 8‐month old boy presented with vomiting and was referred to the otorhinolaryngology team based on his mother's suspicion that her child might have ingested a foreign body. Flexible laryngoscopy revealed a phone screen protector at the vallecular region. The foreign body was removed in the operating theatre. Conclusion Foreign body ingestion should always be suspected in young patients. Consideration of the patient's symptoms, level of lodgement, and type of foreign body will determine whether immediate intervention or a conservative approach is warranted.